MOTIVASI HIDUP PADA PENDERITA LUPUS DEWASA - Aditya Widi Kristanto; TA. Prapancha Hary (JURNAL SPIRITS, 2015)
AbstractThe purpose of this research is to know about life motivation of lupus sufferer when an individual face difficult periods and comes up from the cobdition which is full limitation after the doctor diagnoses lupus disease. Subject of the research is someone who is attacked by lupus. The range of age is from 25 until 35. This research will be held at subject’s house which is in Gombong sub distric, Kebumen district. The methods that are used are observation, interview and the use of triangulation technic to strengthen the result. The result of analyzing data is based on three aspect of motivation, it is concluded that having positive attitude, oriented on achievement of a goal, and streng that motivates an individual becomes one influence that supports life motivation for the subject. Keywords: Motivation, Lupus Sufferer